Pre-service English Language Teachers’ Learning Experiences with E-portfolios for Development and Growth - Khan, Mahbub Ahsan (2010)

(untitled)
In spite of apparent difference, language and literature are interrelated entities and its effective use can facilitate language learners’ development and growth. In Malaysia, at the beginning of new millennium such policy was integrated to boost up the deteriorated standards of ESL students. But, researchers argue that pre-service ESL teachers who came across this initiative are defecating in several fundamental competencies. However, e-portfolio has become a frequent topic of discussion in the contemporary teacher education contexts and considered as the single most persuasive innovation to foster pre-service teachers’ tangible development and growth over time. Despite of that, research on e-portfolio is sparse in Malaysia; particularly it has never been explored in pre-service teacher education context. Hence, this study was initiated focusing on three core issues; (1) pre-service ESL teachers’ perception toward eportfolios, (2) its contributions in their development and growth and (3) the challenges of creating e-portfolios. Fifty five pre-service ESL teachers participated in this study who were majoring in TESOL and enrolled in the course PET301 (Teaching of English through Literature) at the second semester (2008/2009 academic year) in USM. As a course-requirement, participants employed Google Group as online platform and created individual e-portfolios, posted six weekly journals in line with the course contents, and shared ideas through reflective practices.